Business Model Canvas dalam Tinjauan Ekonomi Islam - Rinawati, Ika; Khusnudin, Khusnudin (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
Business Model Canvas (BMC) seems to be in accordance with the demands of the times as a form of innovation in business, this is in accordance with Islamic guidance. This study aims to explain the nine basic blocks in BMC according to the perspective of Islamic economics. The methodology used is library research with a normative approach, analyzing various literature and documents related to BMC in accordance with the book entitled Business Model Generation and Islamic business documents and literature in accordance with the Qur'an and Hadith. The analysis was carried out on the suitability of the characteristics of the nine basic blocks with the normative rules Qur'an and Hadith. The results of this study explain the Islamic economic review of the nine basic blocks of BMC, including: customer segment (determining market segments), value proposition (creating consumer benefits), channel (speed and accuracy of delivery), consumer relationship (not committing ba'i prohibitions), revenue stream (how to obtain wealth and utilize it), key resources (utilization of resources), key activities (realizing noble attitudes), key partnership (maintaining relationships with partners) and cost structure (managing finances fairly).